A escolarização da pessoa com deficiência nas comunidades ribeirinhas da Amazônia Paraense - Fernandes, Ana Paula Cunha dos Santos (2015)
In this doctoral research it is questioned: how does the education of students with special needs who attend schools in riverside communities linked to Belém of Pará system of education? The objective is to analyze the special students educational process who attend schools of riverside communities linked to Belém of Pará metro school system. The methodology approach deals about a historical and dialectical study. The procedures that composed the methodological basis of this work are: literature review, semi-structured interviews, observation (diary and photography), survey and document analysis, social and educational indicators and systematization and analysis of the data. The participants were 04 coordinators, 04 teachers of multifunctional resource room and 05 regular classroom teachers from four islands of Belem: Caratateua, Cotijuba, Combu, Mosqueiro. There were five schools and two teaching units. The results indicated that there is no production involving the theme of this thesis; the INEP data showed a reduction of student with special needs enrollment who lived and studied in the countryside and who lived in the countryside and studied in the city; most of interviewed teachers are effective and female; the data presented by the schools and/ or the teachers are higher than the one presented by the board of education and even by the INEP; There was a difficulty to access the data of some schools from the metro system. About the data from de Pedagogical Unity, only one was showed. All the interviewed teachers have “lato sensu” pos graduate degree e few ones have master degree; charity, depreciation and complacency are concepts that arise when asked about inclusion; some parents do not take their children to the multifunctional clasrooms; in Mosqueiro, there is high demand for students with disabilities in the same classroom on the grounds that there is no other class of the same cycle; there are still some teachers who try to match the student with disabilities to self and to her system experiencing the integration; on the island of Cotijuba, the teacher is itinerant and has no multifunctional resource room with due furnishings; the support team for the multifunctional resource room of the islands of Mosqueiro, Cotijuba and Combu, lies in the inner city of Belem and even with scheduling hardly attend; there is difficulty in having professionals willing to work on the islands, in all areas; on the islands, there is multidisciplinary team for SRM; on the island of Combu; there is no teacher for multifunctional resource room/Special Education, but there are students with disabilities; the multifunctional resource rooms are insufficient for the demands of the island of Mosqueiro; there is a strange relationship between school headquarters and annex; there is education funding proposed by the Department of Education, called "fundinho"; the islands of Cotijuba and Mosqueiro, visualized the collaborative relationship between teachers of common classes and multifunctional resource rooms; the common classroom teachers aim to meet the proposals and suggestions of multifunctional classroom teachers; When necessary, common classroom teachers and multifunctional resource room teachers act together as viewed in Mosqueiro and Cotijuba; it is difficult to teach people with disabilities by the common classroom teachers; However, on the island of Caratateua, there was greater absence of parents; there are reports of violence, family problems and harassment on the islands; transport is insufficient for the demand, and precarious. And yet, there is no necessary adaptations to meet students with disabilities in the boat, in the bus or in the van, including the school bus (School Paths); there are other results listed in this thesis.